Active packaging poly (lactic acid) nanofibers containing essential oils for table grapes: antifungal and physicochemical properties - Brandão, Rafaela Magalhães (2021)
The essential oils (EOs) from Alpinia speciosa, Cymbopogon flexuosus, Ocimum basilicum L and Ocimum gratissimum L. were extracted and the chemical compositions were determined. The nanofibers incorporated with EOs were produced through the solution blow spinning (SBS) of poly (lactic acid) (PLA), they were characterized physicochemically, and the in vitro antifungal and antiocratoxigenic tests against Aspergillus carbonarius, Aspergillus niger, Aspergillus ochraceus and Aspergillus westerdjikiae were performed. The in vivo antifungal effect (grape) of EOs encapsulated in PLA nanofibers against Aspergillus carbonarius and Aspergillus niger as potential active packaging to be applied to control the degradation of table grapes was also studied. The EOs were extracted using the hydrodistillation and characterized by gas chromatography (GC/MS and GC/FID). The nanofibers were produced by the SBS technique and characterized by scanning electron microscopy (SEM), differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR), contact angle and thermogravimetric analysis (TGA). The antifungal and antiocratoxigenic properties were evaluated by the fumigation method. The in vivo test was achieved using a polyethylene terephthalate package for grapes containing the nanofibers, evaluating the physicochemical parameters of the grapes and fungal proliferation after 10 and 20 days of incubation. Terpinen-4-ol (20.23%), sabinene (20.18%), 1,8-cineole (16.69%), γ-terpinene (11.03%); and citral (97.67%) were the principal compounds present in the EOs from A. speciosa and C. flexuosus, respectively. The main constituents from O. basilicum were linalool (26.89%), 1,8-cineol (23.62%) and camphor (15.69%), whereas eugenol (79.04%) was the principal component from O. gratissimum. Electromicrographs showed that the addition of EOs caused an increase in the diameter of the nanofibers. The encapsulation efficiency of essential oils in PLA nanofibers was proven by FTIR results. The DSC curves also indicated the existence of interactions between EOs and polymeric macromolecules through their plasticizing action, resulting in reduced crystallinity of PLA. The hydrophobic character of nanofibers was revealed by the contact angle technique. The efficiency of the PLA nanofiber in controlling the release of essential oils and prolonging the antifungal effect was demonstrated by the TGA technique. The nanofibers provided a significant antifungal effect, decreasing the mycelial growth of A carbonarius (17.86% to 100%), A. niger (10.25% to 100%), A. ochraceus (2.78 to 100%) and A. westerdjikiae (3.64 to 100%). The synthesis of ochratoxin A from A carbonarius (12.09% to 100%), A. niger (8.93% to 100%), A. ochraceus (25.94 to 100%) and A. westerdijkiae (56.26 to 100%) was inhibited in the presence of nanofibers. The fungal proliferation index of A. carbonarius and A. niger in the grapes decreased in the active packages, weight loss, softening and color change were controlled, maintaining the acidity and °Brix parameters, as well as preserving the texture of the grapes. The results indicate that the nanofibers under study can be promising, and they can be applied as active packaging in food for the control of toxigenic fungi and the synthesis of ochratoxin A. They can help to maintain the physicochemical parameters of the grapes, preserve quality, contribute to food safety, and increase the shelf life of the fruits.